The Role of the Microbiota in Regeneration-Associated Processes - Díaz-Díaz, Lymarie M.; Rodríguez-Villafañe, Andrea; García-Arrarás, José E. (Frontiers in Cell and Developmental Biology, 2022)
The microbiota, the set of microorganisms associated with a particular environment or host, has acquired a prominent role in the study of many physiological and developmental processes. Among these, is the relationship between the microbiota and regenerative processes in various organisms. Here we introduce the concept of the microbiota and its involvement in regeneration-related cellular events. We then review the role of the microbiota in regenerative models that extend from the repair of tissue layers to the regeneration of complete organs or animals. We highlight the role of the microbiota in the digestive tract, since it accounts for a significant percentage of an animal microbiota, and at the same time provides an outstanding system to study microbiota effects on regeneration. Lastly, while this review serves to highlight echinoderms, primarily holothuroids, as models for regeneration studies, it also provides multiple examples of microbiota-related interactions in other processes in different organisms.